Internalization Strategy of Tamaddun Melayu Values in Batam Public Senior High School: Strategi Internalisasi Nilai-Nilai Tamaddun Melayu di SMA Negeri 1 Batam - Astri Testiningtyas Firman; Agustina Tri Wijayanti; Sudrajat Sudrajat (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Indonesia’s cultural pluralism encompasses the Tamaddun Melayu civilization, a rich repository of local wisdom and ethical systems currently vulnerable to erosion in the era of globalization. Specific Background: SMA Negeri 1 Batam serves as a strategic site for exploring how educational institutions integrate these values to counter cultural degradation among youth. Knowledge Gap: Existing educational practices often lack structured, multi-dimensional approaches to cultural preservation, creating a disconnect between national character education goals and local implementation. Aims: This study aims to examine the strategies for internalizing Tamaddun Melayu values at SMA Negeri 1 Batam through intracurricular, cocurricular, and extracurricular activities using a phenomenological approach. Results: The findings reveal that schools implement a synergistic model: integrating Malay values into Sociology coursework, utilizing experiential learning through local wisdom exploration, and reinforcing cultural identity via arts and traditional attire. Novelty: By applying Culturally Responsive Teaching (CRT) and Bourdieu’s Habitus Theory, this research demonstrates that a tri-pathway strategy effectively transforms cultural knowledge into incorporated habitus. Implications: The results provide an adaptive model for schools in the Riau Islands to strengthen student cultural identity and character education through structured, community-linked pedagogical practices. Highlights Integration of Malay values within Sociology curriculum establishes a robust conceptual foundation for students. Cocurricular exploration of local wisdom facilitates authentic, experiential learning that effectively deepens cultural habituation. Participation in extracurricular arts and traditional practices solidifies symbolic capital and collective cultural identity among learners. Keywords Tamaddun Melayu; Culturally Responsive Teaching; Local Wisdom; Cultural Habitus; Character Education